Investigating the relationship between social adjustment of mentally retarded children and the quality of life of their parents (Scientific Journal of Research Studies in Future Psychology, 2024)
The aim of this research was to establish a relation between intellectually disabled children’s   motor growth and their social adaptability with caregivers’ quality of life. For this Purpose, a group of 100 educable intellectually disabled children has been selected as our sample group using availability sampling method and to measure social compatibility Asghar Dethatches   questionnaire and to measure quality of life QOL questionnaire have been used. According to the results related to person correlation ، physical health ،social  interaction،environmental  health and  mental   health subscales  are  directly  and meaningfully    related  to their  social  adaptability and physical   health and social interaction   subscales  have  meaningful    and indirect   correlation  with their   social   incompatibility .From   multivariable    Regression analysis   output  to predict caregivers  quality  of life   areas   social  compatibility   according  to intellectually   disabled  children’s   motor  growth  ، it is clear that caregivers  physical   health   ، social interaction  and environmental   health areas   are being   significantly   affected  by  their  intellectually  disabled  children’s motor growth. But mental health area is not affected   by social   compatibility and children’s   motor   growth.